Acorn production in Spanish holm oak woodlands - Gea Izquierdo, G.=700 1 Cañellas, I.; Montero, G.
(En, Es)
Ilus., 94 ref.
Keywords: PRODUCCION; FRUTAS; QUERCUS; QUERCCUS ILEX; SISTEMAS SILVOPASCICOLAS; ESPAÑA; BELLOTAS